Regret in Decision Making under Uncertainty - Bell, David E. (Operations Research, 1982)
Evidence exists that people do not always make decisions involving uncertain monetary rewards as if they were maximizing expected utility of final assets. Explanations for this behavior postulate that the cognitive demands of consistency to such a theory are too great. However, situations exist in which more than mental shortcuts are involved and these anomalies raise questions about expected utility theory as a guide to behavior. This paper explores the possibility that expected utility theory appears to fail because the single outcome descriptor—money—is not sufficient. After making a decision under uncertainty, a person may discover, on learning the relevant outcomes, that another alternative would have been preferable. This knowledge may impart a sense of loss, or regret. The decision maker who is prepared to tradeoff financial return in order to avoid regret will exhibit some of the behavioral paradoxes of decision theory. By explicitly incorporating regret, expected utility theory not only becomes a better descriptive predictor but also may become a more convincing guide for prescribing behavior to decision makers.